2011
DOI: 10.1177/1756285611413825
|View full text |Cite
|
Sign up to set email alerts
|

The interferon beta therapies for treatment of relapsing–remitting multiple sclerosis: are they equally efficacious? A comparative review of open-label studies evaluating the efficacy, safety, or dosing of different interferon beta formulations alone or in combination

Abstract: Interferon beta preparations are the most widely used initial therapies prescribed for patients with relapsingremitting multiple sclerosis. Phase III studies have demonstrated comparable efficacy on clinical measures of disease activity, variable benefits on radiological measures, and good overall tolerability. Subsequent clinical studies have attempted to compare directly the three available interferon beta preparations, reporting both safety and efficacy data. We review the literature on studies evaluating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Three different preparations of IFN-beta are in clinical use. They differ in dose, route, and frequency of IFN-beta administration, but they are comparable regarding clinical efficacy [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Three different preparations of IFN-beta are in clinical use. They differ in dose, route, and frequency of IFN-beta administration, but they are comparable regarding clinical efficacy [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Most reassessments of MS patients receiving interferon beta (IFNβ) treatment occur at 3-to 6-month intervals. 30 This study found differences in the results of using the two different methods for determining individual change in MS patients. The simple SD method assumes a change in performance if the difference score exceeds the group mean of the difference scores by more than 1 SD.…”
Section: Discussionmentioning
confidence: 69%
“…Their survey was discussed in detail by Limmoroth et al [33]. Most of the studies have not revealed any significant differences in the efficacy of the respective interferon beta preparations, which seems to confirm their similar impact on mortality rate.…”
Section: 4mentioning
confidence: 85%